195k views
2 votes
What is K+(-5/3)=-44/3​

User Ego Slayer
by
5.7k points

1 Answer

4 votes

Answer:


\boxed{ \bold{ \huge{ \boxed{ \sf k = - 13}}}}

Explanation:


\sf{k + ( - (5)/(3) ) = - (44)/(3) }

When there is a ( + ) in front of an expression in Parentheses, there is no need to change the sign.

That means the expression remains the same.


\sf{k - (5)/(3) = - (44)/(3) }

Move 5/3 to right hand side and change it's sign


\sf{k = - (44)/(3) + (5)/(3) }

While performing the addition or subtraction of like fractions , you just have to add or subtract the numerator respectively in which the denominator is retained same.


\sf{k = ( - 44 + 5)/(3) }

Calculate


\sf{k = ( - 39)/(3) }

Divide -39 by 3


\sf{k = - 13}

Hope I helped!

Best regards!!

User Enzo
by
6.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.